The Moroccan New Keynesian Phillips Curve : A Structural Econometric Analysis - Belinga, Vincent; Doukali, Mohamed (World Bank, Washington, DC, 2019)
The Phillips curve is central to discussions of inflation dynamics and monetary policy. In particular, the New Keynesian Phillips Curve is a valuable tool to describe how past inflation, expected future inflation, and real marginal cost or an output gap drive the current inflation rate. However, economists have had difficulty applying the New Keynesian Phillips Curve to real-world data due to empirical limitations. This paper overcomes these limitations by using an identification-robust estimation method called the Tikhonov Jackknife instrumental variables estimator. Data from Morocco are used to examine the ability of the New Keynesian Phillips Curve to explain Moroccan inflation dynamics. The analysis finds that by adding more information to the hybrid version of the New Keynesian Phillips Curve model by increasing the number of moment conditions, the inflation dynamics in Morocco can be well-described by the New Keynesian Phillips Curve. This framework suggests that the New Keynesian Phillips Curve would be a strong candidate for short-run inflation forecasting.